"A SWIFT AND AFFORDABLE JUSTICE FOR BRAZIL", A "CODE TO END THE DISTORTIONS OF LAW": THE CIVIL PROCEDURE CODE OF 1939 AND SOME SPEECHES ABOUT THE JUDICIARY - Gustavo S. Siqueira (Revista Eletrônica de Direito Processual, 2017)
This research focuses a period of great normative production of the “Estado Novo”. At that time, Brazilian legislation conceived a Constitution (1937) an new Codes. Through the analysis of the discourses of the press and doctrine of the period, and its contexts, it seeks to understand the expectations, innovations and legal debates that existed in 1939, during the preparation of the Civil Procedure Code. With this in mind, I want to know if that universe of arguments, proposals and concerns created by the new Code.